PERSPEKTIF SANTRI AN NAJAH TERHADAP QS. AL-ANBIYA AYAT 26-28 MENGENAI EKSISTENSI MALAIKAT - Rafika Putri Setyaningsih; Nadya Syafa Chairunnisa; Annisa Endah Prihan Dhini (DAS Institute, 2022)
This study aims to find out about the perspective of the An Najah Islamic Boarding School students regarding the existence of Angels in understanding QS. Al-Anbiya verses 26-28, with its application of faith in Angels, is associated with pesantren activities. This study uses qualitative research that directly plunges into the field and analyzes data obtained from sources. The results of these interviews can be obtained about the students' understanding of the existence of Angels in the activities contained in the Islamic Boarding School and the extent to which the knowledge and practice of students regarding faith in Angels. The results of this study reveal that, firstly, angels are creatures created by Allah SWT from Nur or light, where the duties of angels are different but have the exact nature, namely always being obedient and obedient in carrying out Allah's commands. Second, in the Qur'an, Surah Al-Anbiya verses 26-28 contains the contents of the existence of angels such as the position of angels given by Allah SWT, namely as glorified servants of Allah, angels are different from humans. They do not speak and do orders. Allah SWT can intercede for people who are pleased with Allah SWT. Third, the opinion, understanding, and practice of the An Najah Islamic Boarding School students about the existence of angels in QS. Al-Anbiya verses 26-28 concerning several activities contained in Islamic boarding schools